The Use of PEEK in Implantology: A Narrative Review - Hamdi, Zeineb; Salazar, Rosario Cedeño; Arregui, María; Ortega-Martínez, Jordi (British Journal of Healthcare and Medical Research, 2022)
Purpose: The present paper reviewed the literature on PEEK and its applications in implant dentistry. Materials and Methods: In vivo in human and animal models, in vitro studies, case reports and cases series that evaluated the use of PEEK in implantology were included in this narrative review. Results: There are ever more studies on the best way to apply PEEK in implant dentistry. The mechanical properties of PEEK, which are close to that of bone tissue, are its strength. However, its low osteointegration capacity and surface bio-inertness have limited its clinical translation. PEEK cannot be used as a dental implant. However, some studies have shown that this material could be used for guided bone regeneration; implant abutments for interim restorations, impression devices, or a crown framework. Conclusion: Further research, including in vivo and clinical studies, is needed to determine the feasibility, long-term performance and appropriate indication for this biomaterial.